Stigma Gender dan Motivasi Siswa Laki-Laki dalam Pembelajaran Seni Tari - Fitri Nurhaetin; Lilis Sumiati; Nurwani Nurwani (Universitas Negeri Medan, 2026)
Dance learning at the senior high school (SMA) level still faces significant gender bias challenges. Culturally, dance is often constructed as an activity synonymous with femininity, which results in male students tending to be passive, lacking in confidence, and limiting their involvement during the learning process. Based on this reality, this study aims to explore the manifestations of gender stigma experienced by male students and its implications for their learning motivation. To explore this issue, the study was conducted at SMAN 1 Parongpong, West Bandung Regency, using qualitative descriptive methods through data collection techniques of participant observation, in-depth interviews, and documentation studies. Based on the analysis, it was found that gender stigma manifests implicitly through social perceptions and interactions within the school environment, where this condition directly impacts the low intrinsic motivation of male students. However, this study also revealed important findings that the implementation of an inclusive and gender-responsive learning approach has proven effective in reducing this stigma and increasing the active participation of male students. Thus, this study concludes that the role of teachers is crucial in deconstructing stigma and reconstructing a safe, equal, and meaningful dance learning environment for all students.